2013
DOI: 10.1002/ece3.693
|View full text |Cite
|
Sign up to set email alerts
|

Y‐chromosome evidence supports asymmetric dog introgression into eastern coyotes

Abstract: Hybridization has played an important role in the evolutionary history of Canis species in eastern North America. Genetic evidence of coyote–dog hybridization based on mitochondrial DNA (mtDNA) is lacking compared to that based on autosomal markers. This discordance suggests dog introgression into coyotes has potentially been male biased, but this hypothesis has not been formally tested. Therefore, we investigated biparentally, maternally, and paternally inherited genetic markers in a sample of coyotes and dog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 76 publications
(252 reference statements)
1
32
0
Order By: Relevance
“…A recent analysis of maternally inherited mtDNA and paternally inherited Y‐chromosome markers revealed that the asymmetric introgression of dog genes into north‐eastern coyotes is mediated by male dogs (Wheeldon et al . ). Hybridization of European and African wolves with dogs is also consistently mediated by male dogs and female wolves (Gottelli et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A recent analysis of maternally inherited mtDNA and paternally inherited Y‐chromosome markers revealed that the asymmetric introgression of dog genes into north‐eastern coyotes is mediated by male dogs (Wheeldon et al . ). Hybridization of European and African wolves with dogs is also consistently mediated by male dogs and female wolves (Gottelli et al .…”
Section: Discussionmentioning
confidence: 97%
“…Using twelve autosomal microsatellites, Wheeldon et al . () recently found that coyotes in south‐eastern Ontario have on average 2.3% dog ancestry. Together, these results suggest a limited, but appreciable, amount of coyote–dog hybridization in the recent past (11–24 generations, estimated by vonHoldt et al .…”
Section: Discussionmentioning
confidence: 99%
“…) or Canis species (where dog Y chromosomes are introgressed into coyote populations; Wheeldon et al. ). Cline shifts might possibly also account for the patterns found in poplars, if the lack of differentiation at sex‐linked markers results from the massive introgression of P. alba sex chromosomes into the genomic background of P. tremula (Stölting et al.…”
Section: Discussionmentioning
confidence: 99%
“…The preferential introgression of Y chromosomes from dog to coyote (Wheeldon et al. ), for instance, might be driven by a Y‐A incompatibility, assuming that the dog allele for the autosomal locus involved in the incompatibility is dominant over the coyote allele, and that male migration is strong relative to selection.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, red wolves are believed to be extirpated outside of the North Carolina recovery area, but hybridization between red wolves and coyotes is well documented within that area (Bohling et al, 2016;Hinton, Gittleman, Manen, & Chamberlain, 2018). Further, several previous studies have also shown that eastern coyote populations have interbred with domestic dogs (Adams, Leonard, & Waits, 2003;Wilson, Rutledge, Wheeldon, Patterson, & White, 2012;Wheeldon, Rutledge, Patterson, White, & Wilson, 2013;Monzõn, Kays, & Dykhuizen, 2014). While there is evidence that these hybridization events have been adaptive (vonHoldt et al, 2016), it is important to note that the full genome-wide consequences and the geographic extent of interspecies hybridization have not been documented throughout the entire eastern range.…”
Section: Introductionmentioning
confidence: 99%